2022
DOI: 10.3171/2022.7.jns22934
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of sporadic and neurofibromatosis type 2–associated vestibular schwannoma growth in vitro and in vivo after treatment with the c-Jun N-terminal kinase inhibitor AS602801

Abstract: OBJECTIVE Vestibular schwannomas (VSs) are benign nerve sheath tumors that result from mutation in the tumor suppressor gene NF2, with functional loss of the protein merlin. The authors have previously shown that c-Jun N-terminal kinase (JNK) is constitutively active in human VS cells and plays a central role in their survival by suppressing accumulation of mitochondrial superoxides, implicating JNK inhibitors as a potential systemic treatment for VS. Thus, the authors hypothesized that the adenosine 5ʹ-tripho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Apart from Bevacizumab, no additional effective treatment options for patients with SWN have emerged: a recent Phase 0 trial of Everolimus, a mTor inhibitor, in patients with meningioma demonstrated only partial inhibition of the pathway in treated tumors [36]; a phase II trial for Icotinib, an oral epidermal growth factor receptor tyrosine kinase inhibitor, in 10 NF2 -SWN patients reported only one case of radiographic response [37]. Preclinical studies have shown interesting results on the effect of Brigatinib in established NF2- deficient xenograft meningiomas and a genetically engineered murine model of spontaneous NF2 schwannomas (results of a human clinical trial are pending, NCT04374305) [38] and of the c-Jun N-terminal-kinase (JNK) inhibitor in primary human vestibular schwannoma cultures and xenografts, and a genetic mouse model of schwannoma [39]. Promising results of gene replacement therapies in NF2 -SWN have also recently been published, using direct intratumoral injection of an adeno-associated virus vector expressing merlin in a novel human schwannoma model in nude mice, leading to regression of tumors over a 10-week period [40].…”
Section: Therapeutic Aspects Of Schwannomatosismentioning
confidence: 99%
“…Apart from Bevacizumab, no additional effective treatment options for patients with SWN have emerged: a recent Phase 0 trial of Everolimus, a mTor inhibitor, in patients with meningioma demonstrated only partial inhibition of the pathway in treated tumors [36]; a phase II trial for Icotinib, an oral epidermal growth factor receptor tyrosine kinase inhibitor, in 10 NF2 -SWN patients reported only one case of radiographic response [37]. Preclinical studies have shown interesting results on the effect of Brigatinib in established NF2- deficient xenograft meningiomas and a genetically engineered murine model of spontaneous NF2 schwannomas (results of a human clinical trial are pending, NCT04374305) [38] and of the c-Jun N-terminal-kinase (JNK) inhibitor in primary human vestibular schwannoma cultures and xenografts, and a genetic mouse model of schwannoma [39]. Promising results of gene replacement therapies in NF2 -SWN have also recently been published, using direct intratumoral injection of an adeno-associated virus vector expressing merlin in a novel human schwannoma model in nude mice, leading to regression of tumors over a 10-week period [40].…”
Section: Therapeutic Aspects Of Schwannomatosismentioning
confidence: 99%